Evaluación de la eficiencia en la administración de minerales previo a la utilización de protocolo de sincronización - Jumbo Vélez, Holger Marcelo (2023)
In Ecuador in 2022, cattle registered a decrease of 5.1% compared to 2021; It is observed that the Sierra region concentrates the largest number of cattle with 53.0% of the national total, followed by the Coast with 38.5%, 8.5% belongs to the Amazon, in the province of Loja, there are 86,158 heads of cattle, including cows, which are destined for milk production. The objective of this research is to evaluate in breeding cows the effect of prior parenteral administration of vitamins and minerals on the percentage of pregnancy obtained. After performing an IATF, we worked with two groups of 25 animals each, group 1 applied a dose of ADE3, two doses of minerals by deep intramuscular route 15 and 11 days prior to the start of synchronization, group two It worked directly with the synchronization protocol, the results were that group 1 obtained a significant difference in the following parameters; follicular diameter, expression of heat, repetition of heat, conception rate, concluding that parenteral vitamin/mineral administration positively influences the efficiency of the use of fixed-time insemination protocols, in the cost-benefit analysis the two groups obtained profitability, however, group 1 was superior.